Assessment of Tumor Volume Dynamics and Outcome After Radiosurgery for the Treatment of Vestibular Schwannoma: A Single-Center Experience. Issue 6 (July 2021) - Ermiş, Ekin; Egger, Riccarda; Leiser, Dominic; Anschuetz, Lukas; Raabe, Andreas; Abu-Isa, Janine; Manser, Peter; Aebersold, Daniel M.; Wagner, Franca; Herrmann, Evelyn
Abstract : Objective: To assess the factors affecting early local and audiometric outcomes in vestibular schwannoma (VS) patients treated with stereotactic radiosurgery (SRS). Study Design: A retrospective review of medical records. Setting: Tertiary referral center. Patients: Records of all adult patients who underwent SRS between 2010 and 2016 for the treatment of VS were retrospectively reviewed. Patients treated with microsurgery or multi-fractionation schemes, and those who had neurofibromatosis type 2, were excluded. Intervention: SRS, tumor volume/size measurements. Main Outcome Measures: The impact of tumor volume dynamics on the early local and hearing-related outcomes, together with the factors that influence them following SRS, and comparison of different tumor size measurement methods. Results: From 2010 to 2016, 53 patients underwent single fraction SRS of 12 Gy. Median follow-up time was 32 months (range, 6–79). At the last follow-up, only one patient had clinical progression. Age less than or equal to 65 years ( p  = 0.04; odds ratio [OR]: 0.17; 95% confidence interval [CI]: 0.03–0.93) and baseline pure-tone average (PTA) level less than or equal to 30 dB ( p  = 0.03; OR: 0.90; 95% CI: 0.84–0.96) were associated with maintenance of serviceable hearing. On multivariate analysis, PTA remained significant ( p  = 0.01; OR: 0.04; 95% CI: 0.003–0.45). In patients with a loss of serviceable hearing, the mean volume increase tended to be higher than in the patients whose hearing was maintained. The linear measurement method underestimated, and the A  ×  B  ×  C /2 equation overestimated, the radiological progression compared with 3D-volumetric delineations. Conclusion: During the median observation period of almost 3 years, we reported our early outcome results. Tumor volume increase may have an impact on serviceable hearing loss after SRS. Currently there is no widely accepted method for the evaluation of post-SRS response. Linear measurement and the A  ×  B  ×  C /2 equation produce less reliable estimates of radiological progression compared with 3D-volumetric delineations. Accurate volume measurements with 3D delineations should be considered as part of clinical routine for assessing progression and deciding on salvage therapies.